The influence of service quality and promotion on consumers' purchase decisions: a quantitative study of mcdonald's drive-thru service in palembang, Indonesia - Mufidah Zulfa; Dessy Yunita (Institute of Computer Science (IOCS), 2026)
This study examines the influence of service quality and promotion on consumer purchase decisions at McDonald's Drive-Thru PTC Palembang, Indonesia. The increasing demand for fast-food drive-thru services has intensified competition among quick-service restaurants, making service quality and promotional strategies essential determinants of consumer purchasing behavior. A quantitative research approach was employed using primary data collected from 100 consumers through purposive sampling. The data were analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. The results indicate that service quality has a positive and significant effect on consumer purchase decisions (B = 0.112; t = 3.582; p = 0.001), while promotion exerts a stronger positive influence (B = 0.219; t = 5.567; p < 0.001). Simultaneously, both variables significantly affect purchase decisions (F = 354.011; p < 0.001), explaining 88.0% of the variance (R² = 0.880). These findings suggest that improving service performance while implementing effective promotional activities can strengthen consumers' purchasing intentions and enhance business competitiveness in the fast-food industry. The study provides practical insights for restaurant managers in developing customer-oriented marketing strategies and enriches the literature on consumer behavior within the context of drive-thru services